Sosialisasi Kelayakan Prasarana dan Sarana Sanitasi sebagai Solusi Masalah Kesehatan di Gampong Luthu Lamweu, Kecamatan Sukamakmur, Aceh Besar - Nina Shaskia; Cut Dwi Refika; Febriyanti Maulina (Universitas Syiah Kuala, 2025)
Gampong Luthu Lamweu is located in Sukamakmur District, Aceh Besar Regency. This village is one of the villages in Aceh Besar that is facing stunting problem. Poor sanitation has linked to the incidence of stunting in children. Good sanitation not only prevents infectious diseases but also helps ensure the children to have a healthy environment to grow and develop optimally, thereby reducing the risk of stunting. Based on the census conducted in 2020, Gampong Luthu Lamweu consists of 142 families where 61% of the community are included in KK Prasejahtera, which means that the community experiences difficulties in meeting their basic living needs. Based on observations at Gampong Luthu Lamweu, there are several sanitation facilities and infrastructure in inadequate condition, such as clean water facilities and damaged drainage, as well as poor toilets. This could be a reason that contributes to health problems in the village. It is necessary to provide adequate facilities and infrastructure, but public education needs to be carried out as an effort to educate the public about the importance of sanitation and personal hygiene as well as practical ways to maintain cleanliness. This needs to be accompanied by improvements from the government to improve sanitation facilities in Gampong Luthu Lamweu so that it can support the government's program to reduce stunting rates.